Leishmaniasis and Autoimmunity in Patient with LPS-Responsive Beige-Like Anchor Protein (LRBA) Deficiency - Salami, Fereshte; Shirkani, Afshin; Shahrooei, Mohammad; Azizi, Gholamreza; Yazdani, Reza; Abolhassani, Hassan; Aghamohammadi, Asghar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background/Objective: LPS-responsive beige-like anchor protein (LRBA) deficiency is a combined immunodeficiency and immune dysregulation. The authors present a case report of LPSresponsive beige-like anchor protein (LRBA) deficiency with the history of autoimmunity, enteropathy and visceral leishmaniasis. Sirolimus therapy was started for autoimmunity and enteropathy but was discontinued due to recurrent leishmaniasis. Therefore, a common side-effect of many immunosuppressive drugs in patients with LRBA deficiency is increased susceptibility to infections. Methods: Whole exome sequencing was performed to detect the underlying genetic mutation and Leishmania DNA was detected by the PCR technique in this patient. Results: Whole exome sequencing of the patient reported a homozygous frameshift deletion mutation in the LRBA gene (NM_006726: exon29: c.4638delC, p. S1546fs). Leishmania DNA PCR was positive in this case. Conclusion: Parasite infections manifestations report in LRBA deficiency. Leishmania infections in patients with chronic diarrhea and autoimmunity should be considered for immunodeficiency.
Keywords: leishmaniasis